Enantioselective β-Selective Addition of Isoxazolidin-5-ones to Allenoates Catalyzed by Quaternary Ammonium Salts - Zebrowski, Paul; Röser, Katharina; Chrenko, Daniel; Pospíšil, Jiří; Waser, Mario (Synthesis, 2022)
The enantioselective addition of isoxazolidin-5-ones to the β-carbon of allenoates has been carried out by using a novel spirobiindane-based quaternary ammonium salt catalyst. This protocol, which proceeds under classical liquid-solid phase-transfer conditions, gives access to unprecedented highly functionalized β2,2-amino acid derivatives with good enantioselectivities and in high yields, and further manipulations of these products have been carried out as well.
Keywords: ammonium salt catalysis; organocatalysis; β-amino acids; heterocycles; allenoates